1994
DOI: 10.1159/000247109
|View full text |Cite
|
Sign up to set email alerts
|

DNA Flow-Cytometric Analysis of Basal Cell Carcinomas and Its Relevance to Their Morphological Differentiation: A Retrospective Study

Abstract: DNA flow cytometry (FCM) was performed on archived material of 82 basal cell carcinomas (BCC), using Hedley’s technique. Sixty-five samples were analysed. Biopsy samples were classified in five groups depending on their morphological differentiation: solid, cystic, adenoid, keratotic andmetatypical. Two parameters were studied: proliferative index and DNA index. Statistical analysis revealed that BCC with keratinizing or metatypical differentiation had a greater amount of aneuploidy when compared with BCC with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The incidence of DNA aneuploidy in BCC is much lower (9%-40%) than observed for SCC (Frentz and Moller, 1983;Robinson et al, 1996;Staibano et al, 2001). However, different subgroups of BCC, such as keratotic and metatypical subgroups, have been shown to have much higher aneuploidy rates (Fortier-Beaulieu et al, 1994). Furthermore, Staibano and colleagues (2001) suggested that poor clinical outcome from recurrent/ metastatic hyperpigmented BCCs could be predicted on the basis of aneuploidy and cyclin D1 expression.…”
Section: Dna Ploidy Of Nmscmentioning
confidence: 99%
“…The incidence of DNA aneuploidy in BCC is much lower (9%-40%) than observed for SCC (Frentz and Moller, 1983;Robinson et al, 1996;Staibano et al, 2001). However, different subgroups of BCC, such as keratotic and metatypical subgroups, have been shown to have much higher aneuploidy rates (Fortier-Beaulieu et al, 1994). Furthermore, Staibano and colleagues (2001) suggested that poor clinical outcome from recurrent/ metastatic hyperpigmented BCCs could be predicted on the basis of aneuploidy and cyclin D1 expression.…”
Section: Dna Ploidy Of Nmscmentioning
confidence: 99%
“…Whether this is the explanation for their low metastatic potential remains to be seen . There have been few studies on aneuploidy rates in BCC using cytometry, as well as using classical and molecular cytogenetic methods . Yet, there is no study that would genetically characterize different histopathologic subtypes of BCC.…”
mentioning
confidence: 99%
“…We observed allelic loss of a novel cancer‐associated gene, NAV3 , in 20–25% of BCC and SCC tumors and showed that silencing of the NAV3 gene up‐regulates a number of genes relevant for tumor cell growth in primary human keratinocytes. BCC is known to show a high frequency of non‐clonal, structural chromosomal rearrangements and an increased frequency of DNA aneuploidy, especially in BCC exhibiting infiltrative and superficial multicentric growth patterns (23) and metatypical differentiation (24). Likewise, aneuploidy has been found to associate with local metastasis in SCC as well as in head and neck squamous cell carcinoma (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…To obtain a better insight into the effect of NAV3 silencing, we analysed several post-silencing time points separately, because the point of maximal silencing is not necessarily the optimal time point for monitoring the expression of potential target genes. Post-transfection RNA samples from four different time points (6,24,48 and 72 h) were extracted with RNeasy Micro or Mini Kit (Qiagen, Hilden, Germany) and stored at )70°C. Efficient NAV3 silencing was confirmed by quantitative PCR and Western blot ( Fig.…”
Section: Nav3 Gene Silencing In Vitromentioning
confidence: 99%